Second-Order Nonlinear Optical Properties of Carboranylated Square-Planar Pt(II) Zwitterionic Complexes: One-/Two-Dimensional Difference and Substituent Effect - Wang, Hong-Qiang; Wang, Li; Li, Rong-Rong; Ye, Jin-Ting; Chen, Zhen-Zhen; Chen, He; Qiu, Yong-Qing; Xie, Hai-Ming (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2016)
Zwitterionic complexes have been the subject of great interest in the past several decades due to their multifunctional application in supramolecular chemistry. Herein, a series of internally stable charge-compensated carboranylated square-planar Pt(II) zwitterionic complexes have been explored by density functional theory aim to assessing their structures, the first hyperpolarizabilities, first hyperpolarizability densities, and electronic absorption spectra. It is found that the first hyperpolarizabilities of two-dimensional (2D) structure complexes are much larger with respect to the one-dimensional complex. It is ascribed to the lower transition energy and more obvious charge transfer, which can be further illustrated by their large amplitude and separate distribution of first hyperpolarizability density. In addition, the first hyperpolarizabilities of 2D complexes can be further significantly modified by introducing electron-donating/withdrawing groups on the carborane cage. As a consequence, we believe that these 2D zwitterionic complexes can behave as novel second-order nonlinear optical chromophore with a promising future.